Respuesta :

Answer:

B

Step-by-step explanation:

(look up limit calculator)

a has a limit

b does not exist

c  has a limit

d has a limit

e has a limit

Option D is correct one. Limit doesn't exist for [tex]\lim_{x\to \ 2} \frac{x^{2}-6x +8 }{x-2}[/tex].

When a limit is said to be exist?

The limit of f(x) at x = a is said to be exist if the function approaches the same value from both the sides i.e. LHL =RHL (left hand limit = right hand limit)

According to the question we have,

A. [tex]\lim_{x \to \ 1} \frac{2-x}{x+1}[/tex]

at x =1

LHL = [tex]\lim_{h \to \ 0 } \frac{2- (1-h)}{(1-h)+1}[/tex] = [tex]\frac{1}{2}[/tex]

RHL = [tex]\lim_{h \to \0} \frac{(2-(1+h) }{(1+h)+1)} =\frac{1}{2}[/tex]

Here, RHL = LHL

Hence, limit exist.

B. [tex]\lim_{x \to \ 2} \frac{x^{2} -8}{x-2}[/tex]

at x =2

LHL = [tex]\lim_{h \to \ 0} \frac{(2-h)^{2}-9 }{(2-h)-2}[/tex] =[tex]\lim_{h \to \ 0} \frac{4+h^{2} -9-4h}{2-h-2}[/tex] = [tex]\lim_{h \to \ 0 }\frac{2h-4}{-1} =\frac{-4}{-1} =4[/tex]

RHL = [tex]\lim_{h \to \ 0} \frac{(2+h)^{2} -9}{(2+h)-2}[/tex] = [tex]\lim_{h \to \ 0} \frac{4h +4 +h^{2}-9 }{h} = \lim_{h \to \ 0} \frac{2h+4}{1}[/tex]=4

Here, RHL = LHL

Hence, the limit exist.

C. [tex]\lim_{x \to \ 1} (x^{2} -2x-5)[/tex]

at x =1

LHL = [tex]\lim_{h \to \ 0} (( 1-h)^{2} -2(1-h)-5)= \lim_{h \to \ 0} (1 -2-5)=-6[/tex]

RHL = [tex]\lim_{h \to \ 0} ((1+h)^{2} -2(1+h)-5) = (1-2-5)=-6[/tex]

Here, LHL = RHL = -6

Hence, the limits exist.

D. [tex]\lim_{x \to \ 2} \frac{x^{2}-6x + 8 }{x - 2}[/tex]  

at x =2

LHL = [tex]\lim_{h \to \0} \frac{(2-h)^{2} -(2-h)+8}{(2-h)-2} = \lim_{h \to \ 0} \frac{4+h^{2}-4h-2+h+8 }{(2-h)-2}[/tex] =[tex]\lim_{h \to \ 0} \frac{2h-4+1}{1} =-3[/tex]

RHL = [tex]\lim_{h \to \ 0} \frac{(2+h)^{2} -(2+h) +8}{(2+h)-2} = \lim_{h \to \ 0} \frac{4+h^{2}+4h -2-h+8}{h} = \lim_{h \to \ 0} \frac{2h+4-1}{1} =3[/tex]

Here, RHL���LHL

Hence, the limit doesn't exist.

E. [tex]\lim_{x \to \ 3} (x^{2} -3x-1)[/tex]

at x = 3

LHL = [tex]\lim_{h \to \ 0} ((3-h)^{2} -3(3-h)-1)[/tex] = [tex]9-9-1=-1[/tex]

RHL= [tex]\lim_{h \to \ 0} ((3+h)^{2} -3(3+h)-1)= 9-9-1 =-1[/tex]

Here, RHL = LHL

Hence, the limit exist.

Learn more about limit here:

https://brainly.com/question/8533149

#SPJ2